Forecasting of traffic flow parameters in the planning of highways - Абрамова, Людмила Сергіївна; Ширін, Валерій Вікторович (Technology audit and production reserves, 2015)
Existing methods of forecasting the traffic flow are analyzed. Five types of forecast by period for which it is executed and three groups of models for forecasting approach to traffic flow are marked. It is found that for solving road safety audit at the planning stage of roads are useful methods of long-term forecast. It is proposed to use a balance method, which is based on the use of the incoming data of the traffic composition. Groups of the vehicles as part of the traffic flow are marked, which should be considered when planning and designing roads. To predict the composition of perspective traffic flow it is proposed the method based on Bayesian forecasting. The proposed approach can be applied to the road safety audit at the planning stage of roads.